2020
DOI: 10.1111/ejn.14689
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Parkin, PINK1 and DJ‐1 genes to selective neuronal degeneration in Parkinson's disease

Abstract: Parkinson's disease (PD) is characterised by selective and severe degeneration of the substantia nigra pars compacta and the locus coeruleus (LC), which underlies the most prominent symptoms. Although α‐synuclein accumulation has long been established to play a causal role in the disease, it alone cannot explain the selective degenerative pattern. Recent evidence shows that the selective vulnerability could arise due to the large presence of cytosolic catecholamines and Ca 2+ ions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…In addition to SNCA, mutations in several other genes have been identified that cause rare, familial forms of PD. These genes are primarily involved in the autophagic clearance of intracellular aggregates or damaged organelles, especially mitochondria ( 5 8 ). Genome-wide association studies (GWAS) have also identified common SNPs in several genes related to endolysosomal function, such as GBA and LRRK2, that are associated with increased risk of PD ( 8 11 ).…”
mentioning
confidence: 99%
“…In addition to SNCA, mutations in several other genes have been identified that cause rare, familial forms of PD. These genes are primarily involved in the autophagic clearance of intracellular aggregates or damaged organelles, especially mitochondria ( 5 8 ). Genome-wide association studies (GWAS) have also identified common SNPs in several genes related to endolysosomal function, such as GBA and LRRK2, that are associated with increased risk of PD ( 8 11 ).…”
mentioning
confidence: 99%
“…Both sites are highly conserved and lie close to Cys106 that is modified under oxidative stress conditions, thereby stimulating DJ1 recruitment from the cytosol to the mitochondria (Figure S13A) (Canet-Aviles et al, 2004). Patients with DJ1 mutations resemble PINK1 and Parkin patients (van der Vlag et al, 2020), however, we observed that the reduction of DJ1 ubiquitylation at Lys 93 was PINK1 independent (Figure S13B) and in future work it will be interesting to determine the mechanism of the functional impact of DJ1 ubiquitylation in the context of mitophagic signalling.…”
Section: Discussionmentioning
confidence: 85%
“…Such targets include, of course, α-Syn, but extend to a panoply of mechanisms that might impact upon α-Syn, either in all or subsets of the PD population, these include oxidative stress [18], LRRK2 [19], apoptosis [20], neuroinflammation [21], misfolding proteins [22], age [2], melanin [23] and iron accumulation [24]. The most attractive of these targets also have support from genetic studies, and include LRRK2 [25], parkin, PINK1 [26] and GBA [27]. MicroRNAs are also emerging targets that have gained increased attention in neurodegenerative disorders, including PD [28].…”
Section: The Underlying Mechanisms Of Parkinson's Disease (Pd)mentioning
confidence: 99%